Nixon's war at home : the FBI, leftist guerrillas, and the origins of counterterrorism - Chard, Daniel S. (Justice, power, and politics., 2021)
"Drawing on thousands of pages of declassified FBI documents, Nixon's War at Home shows how America's guerrilla war prompted the FBI to institute a host of new policing measures while reviving illegal spy techniques previously used against communists in the name of fighting terrorism. These efforts did little to stop the guerrillas - instead, they led to a bureaucratic struggle between the Nixon administration and the FBI that fueled the Watergate Scandal and brought down Nixon. Yet despite their internal conflicts, FBI and White House officials developed preemptive surveillance practices that would inform U.S. counterterrorism strategies into the twenty-first century, entrenching mass surveillance as a cornerstone of the national security state"--